Design Curriculum of Islamic Economics Based on Independent Learning Independent Campus (MBKM) to Increase the Competitiveness of Graduates - Imsar Imsar; Rahmat Daim Harahap Imsar; Nurul Jannah; Purnama Ramadani Silalahi; Robi Mufti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The Independent Learning Independent Campus (MBKM) curriculum in the Islamic Economics Study Program has not been implemented optimally. Universities experience many obstacles in implementing the MBKM system, including those related to the conversion of grades and the assignment of grades to the selected subjects, the different curriculum models used, the limitations of teaching lecturers, and the materials to be taught. In this study, the authors use qualitative data types with Primary and Secondary Data Sources. The results of this study indicate that the MBKM implementation can be carried out for students in semester 5 by carrying out a student exchange program and for students in semesters 6 and 7 by carrying out an internship program outside the college. Based on the results of interviews with the Dean and Head of the Islamic economics/sharia economics study program at three well-known universities, namely UIN Syarif Hidayatullah, the Tazkia Institute, and Padjadjaran University, the researchers concluded that the MBKM Program opens opportunities for students to develop their skills, expand their networks and go directly into the world of work. Therefore, in the future, alumni can adapt young and be able to compete with graduates.